Impact of integrated preventive and curative health package on nutritional status of children under 2 years of age in the health area of Tama, Tahoua region (Niger) - Pedrero-Tomé, Roberto; Marrodán, María Dolores; López-Ejeda, Noemí; Escruela, Montserrat; Rocaspana, Merce; Vargas, Antonio; Casademont, Cristian; Gutiérrez, Rui; Lanusse, Candelaria (Frontiers in Nutrition, 2023)
Background: Niger, relevant in light of current political coup, is one of the countries with the worst human development indicators, , characterized by high fertility rates and extremely high infant mortality rates. Food insecurity in the region is alarming, leading to high malnutrition rates in children. This study aimed to evaluate an integral preventive-curative health program targeting children aged under 2 years in the health area of Tama, district of Bouza, Tahoua. Methodology: Anthropometric follow-up data of 6,962 children aged under 2 years were included in this study. These children received complete vaccination and malaria chemoprevention, and those older than 6 months received nutritional supplementation with a small quantity of lipid-based nutrient supplements. Fundamental growth indicators (height-for-age, weight-for-height, weight-for-age, and middle-upper arm circumference) and the Composite Index of Anthropometric Failure were calculated at the beginning and end of the program (mean time spent in the program: 14.5 ± 6.6 months) The evolution of these indicators was compared with those of a sample from a vertical vaccination program conducted in the neighboring region of Madarounfa on similar dates. Results: The proportion of children without anthropometric failure decreased from 59.5% to 40.2% (p<0.001), with the categories that included stunting increasing the most. When analyzing the anthropometric indicators according to the months of compliance with the program, there was a slight improvement in the indicators of acute malnutrition, whereas those of chronic malnutrition worsened significantly. However, when compared with the This is a provisional file, not the final typeset article Madarounfa sample, the children in the present study registered a significantly lower worsening in all three indicators: height-age (-0.46 vs. -2.44; p<0.001), weight-height (+0.31 vs. -0.55; p<0.001) and weight-age (-0.03 vs. -1.63; p<0.001) difference. Conclusion: The comprehensive preventive-curative health program slightly slows the worsening of cumulative malnutrition in the early years of life in complex contexts, such as southern Niger.